Flutuação populacional de Dípteros muscóides (Diptera: muscomorpha), parasitóides e foréticos predadores, Igarapé - MG, 2006 - Magno Augusto Zaza Borges (2006)
Muscoid diptera are considered the biggest problem in poultry farms, having caused direct and indirect damages and, that they reflect in the productivity and the poultry products quality. The present work has as objective to determine the frequency and abundance of the muscoid diptera in a poultry farm, its parasitoids and phoretic predators. The field collections had been carried through in a shed of the aviary of the Hélio Barbosa Farm, of the School of Veterinary Medicine of UFMG, in Igarapé, MG. Traps made with bottles of type PET of one liter had been used; being that in the inferior part had been made punctures to flies enter them. The commercial bait Vetor® was used as attractive (Novartis Biociências S/A), that it consists of a pheromone (Tricoseno) and one insecticide of sudden action (Azametiphós). The captures had been carried through weekly in the months of November of 2004 until October of 2005. 120,876 arthropods during the period of the work had been collected, being of these 104,105 (86.13%) diptera ones. The species most abundant of Diptera was Drosophila repleta, that it represented 54% of the collected species, however its capture practically restricted to the period of December the March (98.77%), that is, during the rainy station. During the period of study 7635 hymenoptera parasitoids had been collected. The families most representative had been Braconidae, Pteromalidae, Diapriidae. The other collected families (Bethylidae, Chalcididae and Icneumonidae) had been grouped as others parasitoids. During the period of the work 5,172 mites of the families Macrochelidae and Uropodidae had been collected. The mites had been collected during all the year, presenting two population peaks in March and August. During the period of study 429 pseudoscorpions, all pertaining Whitiidae family a had been collected. They had been collected during all the year, presenting bigger frequency of November the February, with population peak in December